Monitoring of ECFS quality standards for the clinical management of adults with cystic fibrosis - Gramegna, Andrea; Aliberti, Stefano; Amorim, Adelina; Blasi, Francesco; Bourke, Stephen; Burgel, Pierre-Régis; Diamantea, Filia; Durieu, Isabelle; Fila, Libor; Moreno, Rosa María Girón; Messore, Barbara; Pokojová, Eva; et al. (Journal of cystic fibrosis, 2024)
Background - Although cystic fibrosis (CF) standards of care have been produced and regularly updated, they are not specifically targeting at the adult population. The ECFS Standards of Care Project established an international task force of experts to identify quality standards for adults with CF and assess their adherence. - Methods - This study was composed of two phases. In the first one, a task force of international experts derived from published guidelines and graded ten quality standards for adult CF care using a modified Delphi methodology. In the second phase, an international audit was conducted among adult CF centers to retrospectively validate the quality statements and monitor adherence. - Results - The task force identified 10 quality standards specific to the care of adults with CF, mainly based on the 2018 ECFS standards of care. 14 adult CF centers participated in the audit, which showed that most quality standards for the management of CF in adults are met across Europe. Heterogeneity in adherence to standards was found across centers according to geographical setting and centers’ characteristics. - Conclusions - The identification of quality standards is a valuable resource for the standardization and monitoring of care delivery across centers taking care of adults with CF.
Online verfügbar: 8. November 2023, Artikelversion: 17. Mai 2024
Gesehen am 10.07.2025